2006
DOI: 10.1002/ts.172
|View full text |Cite
|
Sign up to set email alerts
|

Iron toxicity symptoms in yams (Dioscorea spp.) grown in water culture

Abstract: Growth of varieties of Dioscorea alata and D. rotundata were stunted when they were grown in nutrient solutions containing 5 to 60 mg l -1 Fe. In D. alata variety TDa 95/00361, plants grown in 60 mg l -1 Fe solution exhibited reductions of 29-65% in plant height, leaf length and width, number of leaves, stems and roots, and root length compared to the control. The corresponding values for D. rotundata variety TDr 89/02565 were 34-59%. Tuber weight in D. rotundata variety TDr 89/02565 was increased by the iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…According to the findings of Effendy et al (2015), Fe concentration had an effect on the root length of pineapple plants 1-5 weeks after treatment, and root length inhibition occurred as Fe concentration increased. The research by Shiwachi et al (2006) also reported that the level of Fe 60 mg L -1 was able to reduce the number of roots up to 58% compared to controls. Excess iron can damage the root system in rice (Onyango et al 2019).…”
Section: Plant Growthmentioning
confidence: 87%
“…According to the findings of Effendy et al (2015), Fe concentration had an effect on the root length of pineapple plants 1-5 weeks after treatment, and root length inhibition occurred as Fe concentration increased. The research by Shiwachi et al (2006) also reported that the level of Fe 60 mg L -1 was able to reduce the number of roots up to 58% compared to controls. Excess iron can damage the root system in rice (Onyango et al 2019).…”
Section: Plant Growthmentioning
confidence: 87%
“…The results of several studies also reported that increasing the concentration of Fe can reduce plant growth, such as pineapple [18], Vaccinicum macrocarpon [19], soybean [20,21], and Disccorea spp. [22]. Growth inhibition due to Fe toxicity is thought to be caused by an increase in Fe content in plants which interferes with plant metabolic processes and damages plant cell structures [23], and an increase in Fe concentration is able to inhibit nutrient absorption, so that plants experience nutrient deficiency (deficiency).…”
Section: Discussionmentioning
confidence: 99%